2012
DOI: 10.1073/pnas.1120238109
|View full text |Cite
|
Sign up to set email alerts
|

In-feed antibiotic effects on the swine intestinal microbiome

Abstract: Antibiotics have been administered to agricultural animals for disease treatment, disease prevention, and growth promotion for over 50 y. The impact of such antibiotic use on the treatment of human diseases is hotly debated. We raised pigs in a highly controlled environment, with one portion of the littermates receiving a diet containing performance-enhancing antibiotics [chlortetracycline, sulfamethazine, and penicillin (known as ASP250)] and the other portion receiving the same diet but without the antibioti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

93
698
4
4

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 904 publications
(799 citation statements)
references
References 46 publications
93
698
4
4
Order By: Relevance
“…In addition, 5-week PTE treatment decreased the population of Deferribacteres and increased that of Proteobacteria. These changes in gut microbiota profiles were similar to the evidence presented in previous reports for treating obesity with prebiotics (oligofructose) and antibiotics (vancomycin or penicillin) [64,65]. Furthermore, PTE treatment caused a reduction in both Lachnospiraceae and Ruminococcaceae populations, which positively correlate with obesity, in subjects fed a HFD [66,67].…”
Section: Discussionsupporting
confidence: 86%
“…In addition, 5-week PTE treatment decreased the population of Deferribacteres and increased that of Proteobacteria. These changes in gut microbiota profiles were similar to the evidence presented in previous reports for treating obesity with prebiotics (oligofructose) and antibiotics (vancomycin or penicillin) [64,65]. Furthermore, PTE treatment caused a reduction in both Lachnospiraceae and Ruminococcaceae populations, which positively correlate with obesity, in subjects fed a HFD [66,67].…”
Section: Discussionsupporting
confidence: 86%
“…The abundant and diverse ARGs found in antibiotic-free cattle manure are in line with the similar findings in previous studies (Looft et al 2012;Kyselkova et al 2013Kyselkova et al , 2015Wichmann et al 2014), which prompted us to explore the evolution and movement of these ARGs after manure application. Although land application of cattle manure is a common practice in crop production, current knowledge regarding the temporal patterns of ARGs following manure amendment is limited, which hinders our ability to reliably predict ARG behaviors in soil environment.…”
Section: Temporal Patterns Of Soil Args and Stimulation Of β-Lactam-rsupporting
confidence: 62%
“…In the beginning of the study, all faecal samples were positive for the selected resistance genes, although the piglets as well as their dams were never exposed to any antibiotics. A similar situation has been found in previous studies [28,29], which also reported the presence of background resistances in the absence of any antibiotic selective pressure. In our study, resistance gene copy numbers were higher in the pigs as in the sows (unpublished results) but decreased with time which might reflect age related differences in the microbiota.…”
Section: Discussionsupporting
confidence: 71%